PEMANFAATAN EKSTRAK TANIN DAUN KETAPANG SEBAGAI INHIBITOR KOROSI PADA LOGAM DALAM MEDIA HCl 1 M - Nur Fitriana Salsabila; Arfan Maulana; Nurul Widji Triana (KURVATEK, 2023)
A metal degrades through the process of corrosion when electrochemical reactions occur with its surroundings. As long as the metal is exposed to corrosive conditions, the corrosion process will continue to compress the metal, degrading its mechanical properties. The objective of this study is to evaluate the performance and determine the optimum conditions of a corrosion inhibitor extract based on variations in the inhibitor concentration and immersion period. The first step was extracting tanins from ketapang leaves using a 120-minute maseration process (850C temperature and 200 rpm mixing) with a 1:25 solvent ratio. The extract is introduced to the corrosive medium containing the submerged metal in a variation of the immersion period that has been defined for the calculated final weight using the hemp leaf extract concentrations (700, 800, 900, 1000, and 1100 ppm) and the amount of time the samples were submerged (48, 96, 144, 192, and 240 hours) in a 1M HCl solution. The test sample with the addition of an inhibitor concentration of 1100 ppm and a 240-hour immersion time provided the largest results of the experiment with 39.22 % efficiency.